REFLEKSI KEHIDUPAN DALAM IMPLIKASI EDUKATIF IPS - Torkis Dalimunthe (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Social studies education and social sciences always get the spotlight as students who are difficult to be considered by students, because they are confronted with various concepts, theories and facts that must be memorized. Therefore, for social studies teaching, teachers are needed who can teach it well, meaning that they master the material provided, are able to select the right parts to be used as material for conversation, skilled in managing the developing information. In addition it needs to be realized that social studies teachers must be skilled in integrating social sciences to facilitate the achievement of the expected goals together, namely students are skilled in recognizing social problems and ways to solve social problems to the stage of application so that students become active in their community environment, thus be a good citizen.Keywords: Reflection, Educational, Social Sciences Education